The Effectiveness of Corset Use on Pain Reduction in Post Cesarean Mothers - REGINA VT NOVITA; SIMANJUNTAK, EVITA; WIDANI, NI LUH (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The biggest complaint submitted by postpartum mothers is pain. Mothers who have a continuous excessive pain response will have an impact on the mother’s psychology and physique. The physical impact is that the mother feels exhausted, so the wound healing process becomes inhibited. Aim: To evaluate how well corset use reduces pain in post-SC mothers at a South Tangerang private hospital. Methodology: The respondents in this study were post-SC mothers at a private hospital from July 2023 to January 2024 as many as 70 respondents were taken in total sampling, intervention for using corsets during 6-12 hours per day for two days. Assessment of pain before corset use and two days of corset use. This research is a type of Quasy Experiment, one group pre and post test design with paired test analysis test, sample t test &; Chi Square test. Results: The results of the study were the majority of respondents aged 20-35 years (71.4%), Multigravida (58.6%), moderate pain pre-intervention pain scale (57.6%) and in mild pain post-intervention (54.4%). There was no relationship between Age (0.593) and parity (0.138) to reduce the pain for cesarean mothers. The effectiveness of using corsets on pain reduction with pairet t-test obtained p value: 0.000; P<0.05. The t value: 7.622, which means that giving corset intervention to cesarean mothers can reduce the pain scale by 7.6 times compared to not giving intervention. Conclusion: The use of corsets is effective in reducing pain for cesarean mothers at private hospital. Suggestion:It is hoped that hospitals through health workers can provide post-SC maternity nursing care with the use of corsets to relieve pain after SC childbirth and increase postpartum comfort.